Functional protective coatings for improved tool life in cold forging - Engel, Ulf; Hinsel, Christian; Geiger, Manfred (THE Coatings, Proc. of the 1st Int. Conf., 14-15 Oct 1999 Thessaloniki, Greece, 1999)
None
LFT Import::2019-08-05 (2001)